The Sound and Letter Changes of Semsur(Adıyaman) Mouth - Güzel, Åžerif; Alti, Zafer (Humanities Journal of University of Zakho, 2018)
This study aims to reveal the sound and letter changes of Semsur(Adıyaman) mouth. In this way, Semsur is trying to reveal the features of his mouth. Because Adıyaman geographically remains in Northern Kurdistan. This floating Kurdish (Kurmanji) speaks away from centers. Our work aims to identify the voices of Semsur and to reveal falling and changing voices. In this direction, some audio recordings were taken from Semsur. Later, the samples were identified for use in the study from these sound recordings. The samples obtained were classified in the alphabetical order as loud and silent. In this classification, the sounds falling, changing or added were given by examples respectively. Apart from this, some findings related to conjunctions and prepositions were discussed. We also talked about changes in some gender-based appendices. As a result of which Semsur's mouth was exposed to sound changes and differences. we are pleased to express our thanks to İslim Doğan, who has made great efforts in obtaining sound recordings in this study and at the same time our students.